1994
DOI: 10.1148/radiology.193.3.7972814
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced renal cell carcinoma: low complication rate and efficacy of postnephrectomy radiation therapy planned with CT.

Abstract: With CT, radiation can be delivered to the renal bed safely and without undue morbidity. Given the lack of chronic complications associated with the side effects of radiation therapy and uniform local control of cancer in these patients, the role of radiation therapy in patients at high risk for local failure may be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Some studies show a tendency to increased overall survival, but without statistical significance [5,9,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show a tendency to increased overall survival, but without statistical significance [5,9,15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been difficult to compare the results of studies because of a variety of dose fractionation schedules, different total doses, irradiation techniques and patient selection [5,6,9,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have been limited by relatively low postoperative doses used secondary to concerns of late radiation sequelae. Recent studies using more sophisticated radiation techniques have reported fewer treatment-related complications [11,12]. Using CT-based treatment planning, Kao et al [11] retrospectively reported the outcome of postoperative radiotherapy for selected patients with positive surgical margins or perinephric disease extension.…”
Section: Discussionmentioning
confidence: 99%
“…Using CT-based treatment planning, the outcome of postoperative radiotherapy has been retrospectively reported for selected patients with positive surgical margins or perinephric disease extension. The overall local failure rate was 100% as compared to 30% for similar patients who underwent nephrectomy alone [132]. Nevertheless, randomized trials limited to high-risk patients will be required to fully assess the benefit of postoperative radiotherapy in local control.…”
Section: Radiotherapymentioning
confidence: 99%